The Influence of Accounting Information Systems and Human Resource Management on Revenue Improvement in SMEs in Landungsari Village, Dau District, Malang Regency - Hendrik Suhendri; Cakti Indra Gunawan (International Journal of Management and Business, 2025)
This study aims to examine the effects of Accounting Information Systems (AIS) and Human Resource Management (HRM) on income improvement among small and medium-sized enterprises (SMEs) in Landungsari Village, Dau Subdistrict, Malang Regency. The study employs multiple linear regression analysis and applies a saturated sampling technique involving 115 SMEs. The findings indicate that Accounting Information Systems have a positive and significant effect on income improvement among SMEs in the study area. This research contributes to the existing literature by addressing the limited discussion on the implementation of Accounting Information Systems in SMEs and by comparing their role with that of Human Resource Management in enhancing SME performance.